The Relationship Between Enabling Factors and the Intention to Return Among Patients Undergoing Conventional Radiological Examinations at Pariaman Regional General Hospital - Santa Mareta; Oktavia Puspita Sari; Yori Rahmadianti; Abidaturrahmah Abidaturrahmah (Journal of Public Health Indonesian, 2026)
Conventional radiology services are a vital medical support in the diagnosis and treatment of patients. Patient return visit rates serve as a key indicator of service quality, which can be influenced by enabling factors such as facilities, service quality, and location. This study aims to analyze the relationship between enabling factors and patients’ willingness to return for conventional radiology examinations. The study is a quantitative, analytical, correlational study with a cross-sectional design. It was conducted at the radiology department of Pariama Regional General Hospital. The population consisted of 52 patients who returned for follow-up visits during the period of July–September 2024.  The sample consisted of 46 respondents. Data were collected via a questionnaire measured using Likert and Guttman scales, which had been tested for validity and reliability, and were then analyzed using the Chi-Square test. The results showed that the majority of respondents rated the facilities as poor (52.2%) and the service as poor (54.3%), while the location was considered accessible (54.3%). Statistical tests revealed a significant relationship between facilities (p=0.039) and service (p=0.018) and the intention to revisit, whereas location was not associated (p=0.236). These results confirm that improving the quality of facilities and service is a key factor in enhancing patient loyalty toward radiology services.